2003
DOI: 10.1046/j.1365-2273.2003.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal fracture manipulation: a comparative study of general and local anaesthesia techniques

Abstract: Nasal injuries are common conditions treated in either Otolaryngology or Plastic Surgical departments. Manipulation for deformity can be conducted in various ways. The aim of this study is to determine if the anaesthetic technique used for manipulation influences outcomes. Five hundred and fifty-five patients had either local anaesthetic (LA) or general anaesthetic (GA) nasal fracture manipulations in our departments over a 6-year period. Three hundred and twenty-four of these could be contacted and questioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…17,18 Courtney et al conducted a follow-up study of 324 patients who had undergone CRNF and found that revision surgery was required in only 3.2% of those who had initially received general anesthesia, compared with 17.2% of those who had received local anesthesia (p < 0.0001). 19 Almost all of the patients in our series (92.3%) returned to their sport. Patients who experience only a nasal contusion can resume their activity immediately.…”
Section: Discussionmentioning
confidence: 71%
“…17,18 Courtney et al conducted a follow-up study of 324 patients who had undergone CRNF and found that revision surgery was required in only 3.2% of those who had initially received general anesthesia, compared with 17.2% of those who had received local anesthesia (p < 0.0001). 19 Almost all of the patients in our series (92.3%) returned to their sport. Patients who experience only a nasal contusion can resume their activity immediately.…”
Section: Discussionmentioning
confidence: 71%
“…Hence, all patients with a suspected nasal fracture are referred to the ear, nose, and throat department (ENT) where they are seen one to two weeks after injury and reassessed. If there is nasal deformity then manipulation can be undertaken [3][4][5][6] to restore the appearance of the nose and function. 7 The nose is the central and most dominant feature of the face, and even millimetres of nasal deviation are easily evident even to the most casual of observers.…”
mentioning
confidence: 99%
“…Many studies have supported the treatment of simple nasal bone fractures involving the distal portion of quadrangular cartilage by manipulation (MNBS) under local anaesthesia, on presentation or up to 2 weeks after injury. The results have been comparable with manipulation under GA . In cases with nasal bone and septal cartilage fracture, performing only MNB without manipulation of nasal septal cartilage makes the reduced nasal bones heal in the direction of the deviated and fractured septum .…”
Section: Discussionmentioning
confidence: 71%
“…Various studies have employed different tools of satisfaction assessment, but no standardized system has been applied . Patient satisfaction rates following manipulation are variable, ranging between 68% and 87% for nasal cosmesis and 64% and 86% for nasal breathing . Objective tools pertaining to patient's cosmesis and nasal breathing are difficult to design.…”
Section: Discussionmentioning
confidence: 99%